COMPARATIVE INVESTMENT ANALYSIS OF SMALL SCALE BROILERS AND LAYERS ENTERPRISES IN OSUN STATE, NIGERIA - Baruwa, Isiaka Olayinka; Fabode, Ololade A (Journal of Agricultural Sciences (Belgrade), 2019)
The study investigated the investment patterns, costs and returns structures of the layers and broilers production in Osun State, Nigeria; compared the net present worth of small scale broilers and layers production in the study area with a view to determining the differentials in investment returns on both small-scale broilers and layers farms. A multistage sampling technique was employed in selecting respondents for the study Primary data were collected from 180 broilers and layers farms, comprising 90 broilers farms and 90 layers farms from six Local Government Areas in Osun State using a structured questionnaire. The data were analysed using descriptive statistics, budgetary techniques and investment tools. Investment pattern indicated that larger amount of money were invested in capital assets for small scale layers (₦651,274.5) compared to broilers (₦448,068.6). More of personal savings was used to fund small scale layers enterprise compared to that of broilers. In addition, the survival of re-investment in small scale layers depends largely on funds from family members while small scale broilers enterprise depends on retained earnings. Budgetary analysis showed that gross margin of the farmers were ₦166,321.8 and ₦1,150,470.8 for broilers and layers enterprises, respectively. Investment analysis revealed that layers enterprise had higher positive net present value (NPV) and internal rate of return (IRR) value of ₦1,523,692.6 and 64.9 per cent, respectively. In contrast, broilers enterprise had smaller positive NPV and IRR values of ₦961,173.3 and 63.0 per cent, respectively. The study concluded that small scale layers enterprise was found to be more economically profitable compared to small-scale broilers enterprise with higher NPV, IRR value and shorter discounted payback period in Osun State.